Wireless Residential Electric Controller Using Arduino Uno and Bluetooth Module HC-05 - Allan Nelwan; Pinrolinvic Manembu; Alfrets Wauran; Franky Manoppo; Calvin Mamahit (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2023)
This research aims to design electrical installations in residential homes that apply Internet of Things (IoT) technology. An Arduino Uno mini system is the controller whose interface uses the HC-05 Bluetooth module. At the same time, the control uses a cellphone with the Android operating system. The design is based on a research development model, but it is not fully standardized by development research because there are some limitations to the problem. The focus is only on tool design, namely planning, manufacturing, and testing the resulting tool or device. The design results obtained an electrical installation control device with an Android phone. The device is capable of connecting and disconnecting load points remotely and automatically. The control distance is approximately 20 meters according to the Bluetooth specifications used.